On the interpretation of ultrasonic laboratory measurements in anisotropic media - Kovalyshen, Y.; Sarout, J.; Lebedev, Maxim (Society of Exploration Geophysics, 2018)
There is an ongoing debate on whether laboratory ultrasonic measurements in anisotropic media yield phase or group velocities. The main problem here is that the size of the transducers used in the laboratory for ultrasonic measurements is comparable with the size of the rock sample or propagation distance. As a result, it is not clear how to interpret the measured traveltimes of ultrasonic waves. The main question is how to define an appropriate effective travel path, its length, and orientation. To answer this question, we look in detail at the full wavefront generated by a finite-size transducer using a specifically designed experimental setup, and a synthetic material (phenolic grade CE). We devise an algorithm for the interpretation of traveltimes measured in the laboratory with finite-size transducers arbitrarily oriented with respect to the symmetry planes of the material. To illustrate/validate the proposed algorithm, we designed a special testing program. The results of the experiments are presented and turn out to be in very good agreement with the analytical predictions on which we base our interpretation algorithm.